Criteria of enteric insufficiency syndrome in victims with abdominal trauma - B. O. Matviychuk; V. T. Bochar; Yu. Y. Golik; O. M. Bochar; Y. I. Bobilyak; O. R. Horoditsky; O. Yu. Mizyurko; O. R. Feita; O. P. Riling (Сучасні медичні технології)
The analysis of surgical treatment of 208 victims with isolated abdominal trauma was performed. In 33,2% of them during the first 7 days the occurrence of the syndrome of enteric insufficiency syndrome (SEN) was confirmed, in particular in 14,2% with blunt trauma and in 62,1% with penetrating. The 37 factors of development of SEN were evaluated. The statistically significant criteria for the development of enteric insufficiency syndrome in patients with abdominal trauma during the first 7 days were time from the moment of injury to the operation for more than 12 hours; pancreatic injury; the presence of multiple lesions of both the small and large intestine. Also signs of the development of dynamic bowel obstruction, which manifested in the absence of spontaneous peristalsis of the small intestine and its dilation of more than 4 cm.